2021
DOI: 10.1038/s41598-021-98554-z
|View full text |Cite
|
Sign up to set email alerts
|

Computational modeling of thermal combination therapies by magneto-ultrasonic heating to enhance drug delivery to solid tumors

Abstract: For the first time, inspired by magnetic resonance imaging-guidance high intensity focused ultrasound (MR-HIFU) technology, i.e., medication therapy and thermal ablation in one session, in a preclinical setting based on a developed mathematical model, the performance of doxorubicin (Dox) and its encapsulation have been investigated in this study. Five different treatment methods, that combine medication therapy with mild hyperthermia by MRI contrast ($$\gamma -{Fe}_{2}{O}_{3}$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 44 publications
4
20
0
Order By: Relevance
“…The obtained value for IFP is consistent with the experimental investigations of Huber et al 69 and Arifin et al 70 , and the numerical studies of Sefidgar et al 27 , Soltani et al 71 , and Moradi Kashkooli et al 32 , 72 . The IFV amount (median value ~ 0.031 µm/s) is also in good correspondence with numerical studies of Pishko et al 73 , Souri et al 74 , and Zhao et al 75 ; and in the same order with the value reported by experimental study of Homopland et al 76 .…”
Section: Methodssupporting
confidence: 90%
“…The obtained value for IFP is consistent with the experimental investigations of Huber et al 69 and Arifin et al 70 , and the numerical studies of Sefidgar et al 27 , Soltani et al 71 , and Moradi Kashkooli et al 32 , 72 . The IFV amount (median value ~ 0.031 µm/s) is also in good correspondence with numerical studies of Pishko et al 73 , Souri et al 74 , and Zhao et al 75 ; and in the same order with the value reported by experimental study of Homopland et al 76 .…”
Section: Methodssupporting
confidence: 90%
“…The mean spatial value of tumor IFP for the networks 1–6 is 1525.7 Pa, 1585.5 Pa, 1698.3 Pa, 1570.2 Pa, 1700.7 Pa and 1868.2 Pa, respectively. The results are good compatible with the numerical studies of Soltani et al 61 , Souri et al 62 , Al-Zu’bi and Mohan 63 as well as the experimental study of Butcher et al 64 , which demonstrated the range of 586–4200 Pa for IFP in the tumor. Moreover, the IFP value in normal tissue is around 53.7–97.5 Pa, that agrees with the values of the experimental study 65 , 66 , which demonstrated the range of − 400 to 800 Pa for IFP in normal tissue.…”
Section: Resultssupporting
confidence: 89%
“…Indeed, the maximum value of IFV occurs at the boundary between tumor and normal tissue where there is a large IFP gradient. IFV results are in the same order as the prediction of Jain et al 38 , Soltani et al 61 , Souri et al 62 , Kashkooli et al 67 , and experimental observation of Hompland et al 68 .
Figure 8 Interstitial fluid velocity distribution for six considered networks.
…”
Section: Resultssupporting
confidence: 80%
“…In free injection of drugs, they can damage non-infected cells, while higher doses can cause some organs to become ineffective. The unique properties of nanocarriers such as good solubility, biocompatibility, long circulation time, as well as surface performance, make them an excellent candidate for the delivery of therapeutic agents [ 28 , 244 , 245 ]. Different types of nanocarriers have been introduced for drug delivery applications ( Figure 12 ).…”
Section: Treatmentmentioning
confidence: 99%